Complexation key to a pH locked redox reaction - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Shams, Tahir; Khan, Khaliquz Zaman (Journal of Chemical Education, 2016)
An unfavorable pH can block a feasible electron transfer for a pH dependent redox reaction. In this experiment, a series of potentiometric titrations demonstrate the sequential loss in feasibility of iron(II) dichromate redox reaction over a pH range of 0-4. The pH at which this reaction failed to occur was termed as a pH locked reaction. The comparative ability of 10 selected iron binding ligands with varied propensity for the redox potential modification of Fe(III)/Fe(II) redox couple to restore/unlock the pH locked redox reaction is shown using potentiometric titrations. The spectrophotometric speciation analysis of Fe(III) Tiron complexation with pH was carried out to explain the differing ability of EDTA and Tiron to unlock the reaction under different pH Conditions. The experiment illustrates how environmental, biological redox reactions avoid severe laboratory conditions to occur and can be explored in the design of novel redox systems for natural attenuation of environmental toxins to their non- or lesser-toxic forms. The experiment also demonstrates prudent laboratory practice for safe waste disposal.
Keywords: Analytical Chemistry; Aqueous Solution Chemistry; Coordination Compounds; Oxidation/Reduction; pH; Physical Chemistry; Potentiometry; Second-Year Undergraduate; Thermodynamics; Titration/Volumetric Analysis; Upper-Division Undergraduate

Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure